Assessing learning style preference of working professional cohorts in India: an empirical study using Honey-Mumford's learning style questionnaire. (2018) - Kumar, Ranjan; Pande, Neerja
Even though the learning needs of working professionals have become more context-centric and application-oriented, scant research has been conducted in India on their learning style preferences. This inadequate understanding of what learning styles and approaches align best with various professional cohorts, predisposes the design and delivery of a learning intervention to being more output-oriented instead of outcome-oriented. This paper is based on an empirical study of working professionals in India ( n = 155) to assess their learning style preferences, by deploying Honey-Mumford's learning style questionnaire (LSQ). The study provides critical insights into learning style preference of various working professional cohorts in India, in terms of functional specialisation, level of education and work experience tenure. The outcome of this research provides critical inputs which can be factored into the design and delivery of outcome-centric learning interventions for working professionals in India.